The Effects of Transformational Leadership, Service Digitalization, and Human Resource Development on Employee Job Satisfaction at the Madiun Regency Population and Civil Registration Office - Adella Nurlita Firdausy; Sri Hartono; Titi Rapini (Golden Ratio of Data in Summary, 2026)
This study analyzed the effects of transformational leadership, service digitalization, and human resource development on employee job satisfaction at the Madiun Regency Population and Civil Registration Office. A quantitative approach was used. Primary data were collected by distributing questionnaires to 43 respondents. The analysis included research instrument testing, classical assumption testing, hypothesis testing, and multiple linear regression analysis. The findings showed that: (1) transformational leadership had a significant effect on job satisfaction, as indicated by a calculated t value of 5.166, which exceeded the critical t value of 1.685, and a significance value of 0.000, which was below 0.05; (2) service digitalization had a significant effect on employee job satisfaction, with a calculated t value of 2.097, which exceeded the critical t value of 1.685, and a significance value of 0.042, which was below 0.05; (3) human resource development had a significant effect on employee job satisfaction, with a calculated t value of 2.744, which exceeded the critical t value of 1.685, and a significance value of 0.009, which was below 0.05; and (4) transformational leadership, service digitalization, and human resource development jointly had a significant effect on employee job satisfaction, as indicated by a calculated F value of 25.335, which exceeded the critical F value of 2.85, and a significance value of 0.000, which was below 0.05.